Konflik Gerakan Masyarakat Sipil dan Pemerintah dalam Proses Penyusunan RUU Cipta Kerja - M. Masad Masrur (Neolectura, 2021)
The discussion room for the Work Creation Bill is officially located at the DPR RI Building. The discussion, which involved various interest groups, was deemed insufficient to accommodate the “rejecting” aspirations expressed by various community groups. Several community groups who are members of various civil society movements, held demonstrations outside the DPR RI Building as a venue for discussion of the Job Creation Bill. Demonstrations that also took place in these areas have caused damage to public facilities. According to Habermas's opinion, this condition is the result of structural domination, where the ruling group directs various forms of policy with instrumental communication that will not create understanding. In agreement with Gramsci, in this case, there is a political hegemony between one group against another. The government, which has an interest in immediately completing the deliberation of the Job Creation Bill, through the power of political domination, seeks to exercise hegemony against the civil society movement, causing violent conflict. Conflict resolution in the discussion of the Work Creation Bill is structurally carried out by using the state law approach in accordance with the prevailing laws and regulations. In accordance with the mandate of the constitution, all matters relating to regulations, a judicial review can be carried out at the Constitutional Court.